Design, development and evaluation of a game-based learning application for room housekeeping - Tan, Fui Ming; Siti Normaziah, Ihsan; Nor Maizana, Mat Nawi; Mohd Razali, Nor Amira (Asian Scholars Network, 2024)
The transition of practical skills training into a digital format presents distinct challenges and opportunities within the hospitality industry. This study explains the development of an online simulation game specifically crafted to educate hospitality students in room housekeeping. The objective is to seamlessly integrate theoretical knowledge with practical application through a virtual platform that simulates real-life housekeeping scenarios. The methodology was structured into three phases: design, development, and evaluation. In the design phase, the game was tailored to meet educational objectives pertinent to hospitality studies, focusing on essential skills such as attention to detail, customer service, and operational efficiency. The development utilized advanced game engines for rendering realistic 3D environments and interactive gameplay to ensure an engaging user experience. The evaluation phase was particularly significant, involving technology acceptance testing by 40 students from a hospitality and tourism course. This test aimed to evaluate not only the game's educational impact and usability, but also its acceptance among users. Preliminary results from the testing indicated strong engagement and improved learning outcomes among participants. The simulation not only allowed students to practice essential housekeeping skills but also promoted critical thinking and problem-solving within a risk-free environment. The paper concludes with a discussion on potential enhancements such as incorporating adaptive learning algorithms and multiplayer features to support collaborative learning. The scalability of the simulation into other areas of hotel operations is also explored, underscoring its potential as a versatile educational tool in hospitality training.